2020
DOI: 10.1167/jov.20.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotopic and saccade-specific transsaccadic memory for object detail

Abstract: The content and nature of transsaccadic memory are still a matter of debate. Brief postsaccadic target blanking was demonstrated to recover transsaccadic memory and defeat saccadic suppression of displacement. We examined whether blanking would also support transsaccadic transfer of detailed form information. Observers saccaded to a peripheral, checkerboard-like stimulus and reported whether an intrasaccadic change had occurred in its upper or lower half. On half of the trials, the stimulus was blanked for 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…In this study, we investigated the perception of shape changes during saccadic eye movements and its relationship to pre- and postsaccadic appearance of shape. Our results confirm that transsaccadic perception of shape changes underlies the same effects that apply to similar ( Deubel et al, 2002 , Experiment 3; Grzeczkowski, van Leeuwen, et al, 2020 ) and other object features: performance at intrasaccadic change detection was relatively poor under normal conditions (no-blank condition) and an accompanying postsaccadic blank facilitated change detection ( Fig. 3B ).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we investigated the perception of shape changes during saccadic eye movements and its relationship to pre- and postsaccadic appearance of shape. Our results confirm that transsaccadic perception of shape changes underlies the same effects that apply to similar ( Deubel et al, 2002 , Experiment 3; Grzeczkowski, van Leeuwen, et al, 2020 ) and other object features: performance at intrasaccadic change detection was relatively poor under normal conditions (no-blank condition) and an accompanying postsaccadic blank facilitated change detection ( Fig. 3B ).…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with previous studies (e.g. Deubel et al, 1996; Goktepe & Schütz, 2023; Grzeczkowski, Deubel, & Szinte, 2020; Grzeczkowski, van Leeuwen, et al, 2020; Hübner & Schütz, 2021; Poth & Schneider, 2016; Tas et al, 2021; Weiss et al, 2015) we observed greater precision in the blanking condition in the change discrimination task of our first experiment. However, the change direction bias was preserved in both blank and no blank conditions.…”
Section: Discussionsupporting
confidence: 93%
“…To understand the limitations and biases of change perception, it is essential to understand how information is processed across saccades. Presaccadic information about SF (Weiss et al, 2015), orientation (Ganmor et al, 2015; Grzeczkowski, Deubel, & Szinte, 2020; Stewart & Schütz, 2018; Wolf & Schütz, 2015), and other visual features of the saccade target can be transferred across saccades and integrated with postsaccadic information (shape - Demeyer et al, 2011; Grzeczkowski, van Leeuwen, et al, 2020; numerosity - Hübner & Schütz, 2017; color - Schut et al, 2018; Wijdenes et al, 2015; Wittenberg et al, 2008). At the same time, the precise nature of transsaccadic integration remains uncertain.…”
Section: Methodsmentioning
confidence: 99%
“…Under hierarchical models of visual processing, after an initial feedforward sweep of visual information, higher level areas, such as the frontal eye fields, use corollary discharge to provide spatiotemporally precise predictions for lower levels within the visual hierarchy ( Schall et al, 1995 ; Stanton et al, 1995 ; Grzeczkowski et al, 2020 ). This ensures that visual stimuli are aligned with their expected post-saccadic retinotopic location despite saccades interrupting the typical flow of visual information.…”
Section: Discussionmentioning
confidence: 99%